Translucidez de resinas compostas constituídas por diferentes monômeros em meios e tempos de armazenamento distintos - Kaizer, Marina da Rosa (2010)
The aim of this study was to determine translucency of composite resins formed by different monomers when stored in two distinct environments (immersed in dis tilled water and red wine) and periods of time (immediately after curing, 24h and 30 days). Also two methods for translucency evaluation (Translucency Parameter and Percentage of Opacity) were compared. Three composite resins were tested: one silorane-based (Filtek P90) and two metacrilate-based (Filtek Z350 and Rok). Fourteen specimens (sp) were made for each composite using a metallic matrix with 10 mm of diameter and 2 mm of thickness. Immediately after light curing using a LED (±800mW/cm2) for 40 seconds, sp were polished with Sof-Lex Pop On Orange Series discs and with felt and diamond paste, then sp were washed in water and dried. Immediately after polishing, the initial translucency was measured with the spectrophotometer SP60 - X-Rite using the CIE L * a * b * system. Then the sp of each composite resin was divided into two groups (n = 7) according to the storage media. Successive readings were conducted in periods of 24 hours and 30 days. Data were submitted to ANOVA and Tukey s test (5%) to compare the means of the groups. The silorane-based composite resin showed less translucency changes than metacrilate-based resins, only when stored in wine. In deionized water the modification of P90 was greater than other resins, improving the translucency. All composites presented more alteration when stored in wine than in water, and such variation was higher in longer periods of storage. No differences were found between the methods of evaluation. Both methods of translucency evaluation demonstrated similar results. The translucency of composites was more affected by the red wine than by the water and the longer the period of contact with this substance the greater the modification. The type of monomer seems to be a factor that will influence the translucency changes of composite resins. The variation of translucency can be measured by the two tested methods